Deteksi Dini dan Penapisan Kadar Asam Urat Usia Produktif di SMA Kalam Kudus II, Jakarta - Sim, Alfred Sutrisno; Goh, Daniel; Gracieene Gracienne (jurnal ABDIMAS Indonesia, 2024)
Uric acid is an end product of purine metabolism that can crystallize at high concentrations, causing gout and other related conditions. This study aims to describe the proportion and risk factors for hyperuricemia in the productive age population. This descriptive research was conducted in March 2024 at Kalam Kudus II High School, Duri Kosambi Village, using purposive sampling techniques. The sample consisted of 74 respondents aged 18-64 years. Data collection includes demographic characteristics and uric acid levels using the Point Of Care Testing (POCT) tool. The results showed that 67 respondents (90.5%) had normal uric acid levels, while 7 respondents (9.5%) had hyperuricemia. Identified risk factors include a high-purine diet, obesity, metabolic syndrome, certain medical conditions, and genetic factors. The results of this research are the importance of changing diet, weight loss, adequate hydration, and the use of medication in managing uric acid levels. Health education has proven important for improving patient compliance with diet and medication, as well as preventing complications. Therefore, it is necessary to develop comprehensive educational programs and further research to improve the treatment of hyperuricemia.